(untitled) (CIPEEX, 2026)
This study evaluated the compressive strength of cementitious mixtures incorporating graphene, assessing the mechanical effects of adding different nanomaterial contents (0.5%, 1.0%, and 2.0%) compared to a reference formulation without graphene. Tests were carried out at 2, 7, and 28 days of curing, enabling an analysis of performance evolution over time. Results showed that the presence of graphene positively influenced sample behavior, with significant strength gains, especially after the seventh day, when microstructural effects became more evident. Mixtures containing 1.0% and 2.0% exhibited the best performance, particularly at 28 days. A change in the failure mode was also observed, with less brittle and more ductile behavior, indicating a more cohesive and homogeneous internal matrix. These improvements can be attributed to three mechanisms associated with graphene’s action: the “filler” effect, enhancing matrix compaction; the acceleration of hydration reactions through physicochemical interactions with cement products; and the densification of interfacial transition zones. Thus, the study highlights graphene’s potential as a functional additive in cementitious materials engineering, pointing to promising pathways for developing high-performance composites with improved durability, mechanical strength, and long-term microstructural stability.